Analisis Miskonsepsi Siswa Berdasarkan Gender dalam Pembelajaran Fisika dengan Menggunakan Tes Diagnostik Two-Tier di Kotabaru - Muhammad Ali (STKIP Paris Barantai, 2019)
The general objective of this study is to describe the relationship between the level of student misconception based on gender in the State High School in Kotabaru South Kalimantan District on physics learning, namely Static Fluid material. The research method used is quantitative descriptive. This research was conducted from September to November 2018 in 10 Public High Schools in Kotabaru Regency. The sample in this study amounted to 500 students consisting of 270 female students and 230 male students. The data of this study were obtained through two-tier diagnostic test instruments and the results of the study were analyzed descriptively. the average percentage of male students' misconceptions is 64% with a high category and female students of 35% which is in the medium category. Based on the learning indicator shows that the highest percentage of misconception in male students is in indicator 6 which is equal to 67% in the high category, and female students are in indicator 2 which is 43% in the moderate category. Based on the results of the research that has been done, it can be concluded that in general gender affects the level of misconception of high school students in Kotabaru, South Kalimantan. Keywords: Misconception, gender, static fluid, two-tier diagnostic test.